2001
DOI: 10.1080/00034980120053258
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of the cysts of Echinococcus granulosus in domestic herbivores from Benghazi, Libya, and the reactivity of antigens produced from them

Abstract: Unilocular cysts produced by Echinococcus granulosus were recovered from 110 domestic herbivores (60 sheep, 25 cattle, 20 goats and five camels) slaughtered in Benghazi. The proportion of the cysts from the sheep found to be fertile (75%) was higher than that of the cysts from the goats (55%), camels (40%), or cattle (0%). When tested in indirect haemagglutination assays (IHA) with eight sera from human cases of cystic echinococcosis, the fluid from the cattle cysts never gave a positive reaction. Antigens in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Scala et al (2006) and Ahmed et al (2006) also showed that in sheep, pulmonary fertile cysts were higher than those in liver. Khan et al (2001) reported that in sheep the fertility of cysts in the liver was similar to that of the cysts in the lungs.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Scala et al (2006) and Ahmed et al (2006) also showed that in sheep, pulmonary fertile cysts were higher than those in liver. Khan et al (2001) reported that in sheep the fertility of cysts in the liver was similar to that of the cysts in the lungs.…”
Section: Resultsmentioning
confidence: 86%
“…In many countries, fertility rate of cysts and viability rate of protoscoleces in different animals have been studied (Khan et al, 2001;Scala et al, 2006;Ahmed et al, 2006).…”
Section: Resultsmentioning
confidence: 98%